2022
DOI: 10.3389/fpsyg.2022.1009173
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of AI algorithmic agents: The impact of algorithmic decision autonomy on consumer purchase decisions

Abstract: Although related studies have examined the impact of different images of artificial intelligence products on consumer evaluation, exploring the impact on consumer purchase decisions from the perspective of algorithmic decision autonomy remains under-explored. Based on the self-determination theory, this research discusses the influence of the agent decision-making role played by different AI algorithmic decision autonomy on consumer purchase decisions. The results of the 3 studies indicate that algorithmic dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…This includes examining the output of algorithms, such as loan approvals or career opportunity allocations, to see if there are unfair or unequal outcomes. If it is found that certain groups are being treated unfavourably, then this may be a sign of unintentional discrimination ( Fan and Liu, 2022 ).…”
Section: Judicial Review Of Algorithmic Discriminationmentioning
confidence: 99%
“…This includes examining the output of algorithms, such as loan approvals or career opportunity allocations, to see if there are unfair or unequal outcomes. If it is found that certain groups are being treated unfavourably, then this may be a sign of unintentional discrimination ( Fan and Liu, 2022 ).…”
Section: Judicial Review Of Algorithmic Discriminationmentioning
confidence: 99%
“…Building on communication theory, Osburg et al (2019) developed and tested a framework illustrating the relationship between morality and purchase decisions. Based on self-determination theory, Fan and Liu (2022) explored the impact of the decisive role on consumer purchase decisions for different AI algorithmic decision autonomy induced. In recent years, some studies have shown that consumer satisfaction has a certain impact on customers' purchase decisions (Hult et al, 2019;Guo et al, 2017b).…”
Section: Purchase Decision Theorymentioning
confidence: 99%